Continuous infusion of recombinant factor VIII formulated with sucrose in surgery: Non‐interventional, observational study in patients with severe haemophilia A. (2nd December 2014) - Meijer, K.; Rauchensteiner, S.; Santagostino, E.; Platokouki, H.; Schutgens, R. E. G.; Brunn, M.; Tueckmantel, C.; Valeri, F.; Schinco, P. C.
Summary In haemophilia A, continuous infusion (CI) of FVIII perioperatively provides a more constant FVIII level than conventional bolus injections, avoiding low trough levels that could increase bleeding risk. Due to the low number of surgical cases in clinical trials, especially in haemophilia, more information on the clinical practice of CI from observational studies is helpful. We aimed to evaluate the effectiveness and safety of CI with recombinant factor VIII formulated with sucrose (rFVIII‐FS) in a typical surgery practice setting. This was a non‐interventional study in 12 centres. Patients with severe haemophilia A who received rFVIII‐FS by CI during and after surgery were included in this study if they had more than 150 exposure days (EDs) to any FVIII product and had no history of inhibitors before CI. Patients were observed during the entire course of CI, with monitoring up to 3 months thereafter. Twenty‐five patients with 28 surgeries were included in the analysis. Median age was 51.7 (range 10–75). Most (75%; 21/25) patients underwent orthopaedic surgeries. The median dose of rFVIII‐FS consumed during CI was 376 IU kg−1 (range 157.9–3605.6 IU kg−1) with a greater median dose for orthopaedic surgeries (424.0 IU kg−1) compared to non‐orthopaedic surgeries (278.5 IU kg−1). 95% of all FVIII measurements (214/224) were on target. Efficacy and tolerability were rated as good/excellent in 89.3% (25/28) of surgeries. No inhibitors were observed during or after surgery. This study demonstrates the effectiveness of CI with rFVIII‐FS during surgery in patients with severe haemophilia A in a clinical practice setting.